Vitamin D and skeletal muscle: A narrative review focusing on chronic kidney disease and dialysis - Vogt, Barbara Perez [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP] (Wiley, 2021)
Morphological, molecular, and physiological effects of vitamin D on skeletal muscle have been analyzed both in animals and humans. Vitamin D may be a potential therapeutic for increasing muscle mass and function. The presence of vitamin D receptors in skeletal muscle cells is already established. However, there is still need for more evidence about the effect of vitamin D on muscle. Some studies have associated vitamin D and skeletal muscle in chronic kidney disease (CKD) patients; most of these studies enrolled hemodialysis patients. FGF-23 and Klotho were recently described in mineral and bone disorders in CKD, resulting in reductions in calcitriol levels. Therefore, both Klotho and FGF-23 may play a role in muscle loss in CKD, which is related to morbidity and mortality risk. Therefore, this article presents a narrative review, aiming to discuss the available information associating skeletal muscle and vitamin D, highlighting the results in CKD and dialysis patients.
Keywords: cholecalciferol; hemodialysis; Klotho; muscle strength; skeletal muscle mass